Logic and the laws of Thermodynamics - Blanco Pérez, Carlos Alberto (THÉMATA. Revista de Filosofía, 2018)
The paper illustrates the possibility of relating the fundamental laws of logical thinking with the basic principles to thermodynamics. According to this hypothesis, the idea of a “transcendental realm” that hosts the a priori categories of understanding is no longer needed, because human logic can be regarded as the result of a process of fine-tuning in our mind’s ability to perceive of patterns of identity and change in nature.